2013
DOI: 10.1016/j.bmcl.2013.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiproliferative activities of quebecol and its analogs

Abstract: Simple and efficient synthesis of quebecol and a number of its analogs was accomplished in five steps. The synthesized compounds were evaluated for antiproliferative activities against human cervix adenocarcinoma (HeLa), human ovarian carcinoma (SKOV-3), human colon carcinoma (HT-29), and human breast adenocarcinoma (MCF-7) cancer cell lines. Among all the compounds, 7c, 7d, 7f, and 8f exhibited antiproliferative activities against four tested cell lines with inhibition over 80% at 75 μM after 72 h, whereas, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…For example, quebecol is a phenolic compound from maple syrup 27 that possesses anti-inflammatory 28 and anti-proliferative properties. 29 A variety of phenolic derivatives from maple syrup demonstrate free radical scavenging activity superior to that of vitamin C. 3 Several polyphenolic molecules present in maple syrup show anti-proliferative effects through arresting cell cycles, suggesting potential effects in cancer prevention. 30 In addition, in vivo studies on phenolic-enriched maple syrup extracts have shown promising therapeutic potential for liver protection, 31 anti-inflammation 32 and anti-diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, quebecol is a phenolic compound from maple syrup 27 that possesses anti-inflammatory 28 and anti-proliferative properties. 29 A variety of phenolic derivatives from maple syrup demonstrate free radical scavenging activity superior to that of vitamin C. 3 Several polyphenolic molecules present in maple syrup show anti-proliferative effects through arresting cell cycles, suggesting potential effects in cancer prevention. 30 In addition, in vivo studies on phenolic-enriched maple syrup extracts have shown promising therapeutic potential for liver protection, 31 anti-inflammation 32 and anti-diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…e reaction mixture was stirred for 24 hours at room temperature, the solvent was removed in vacuum, and the residue was washed with diethyl ether and dried in vacuum. (6-hydroxybenzo[d] [1,3] (6-hydroxybenzo[d] [1,3] (6-hydroxybenzo[d] [1,3] [4]resorcinarenes 10a,d [27,41]. To a mixture of 1.25 mmol pyrrolidine-1carboxamide 1 and appropriate 0.16 g (1.25 mmol) 2methylresorcinol in 5 ml dry chloroform, 2 ml trifluoroacetic acid was added.…”
Section: General Methods For the Synthesis Of Diarylbutanesmentioning
confidence: 99%
“…Diarylmethane derivatives containing two phenolic moieties are of interest due to their wide spectrum biological activity. ese compounds are known to inhibit C-C chemokine receptors [1], possess anti-inflammatory [2], antiproliferative [3], antimicrobial [4], anti-HIV [5], and anticancer activity [6]. Some compounds of this class exhibit antibacterial properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…图 3 机理探索实验 Figure 3 Experiments for probing the reaction mechanism 5). 传统合成方法路线较长 [24] , 或需要 -78 ℃的低温条件 [25] . 本路线合成步骤少, 原料简单 易得, 条件温和, 操作更简便.…”
Section: 引言unclassified